Visual Morbidity and Ocular Complications in Presumed Intraocular Tuberculosis: An Analysis of 354 Cases from a Non-Endemic Population. (18th August 2018) - Gunasekeran, Dinesh Visva; Gupta, Bhaskar; Cardoso, Joao; Pavesio, Carlos E.; Agrawal, Rupesh
ABSTRACT: Purpose : To describe the visual morbidity associated with intraocular tuberculosis (TB) and to report ocular complications of intraocular TB. Methods : Retrospective cohort study of patients diagnosed with intraocular TB at a tertiary referral eye care hospital in central London. Data on baseline and final best-corrected visual acuity (BCVA) along with ocular complications were collected and analyzed. Results : In total, 354 patients with intraocular TB were included in this study. Mean age was 48.45 years (range 19–94) and follow-up was 22.56 ± 7.44 (range 6–30) months post cessation of therapy. Blindness as defined by the World Health Organization was reported in 11 (3.11%) patients at baseline and 13 (3.67%) patients at follow-up. The most common ocular complications were cystoid macular edema ( n = 107, 30.5%) and glaucoma ( n = 99, 28.12%). Conclusion : Intraocular TB can be associated with significant ocular morbidity. Early recognition, treatment, and regular follow-up of this complex disease may help to reduce visual morbidity and ocular complications.